2020
DOI: 10.1038/s41598-020-58551-0
|View full text |Cite|
|
Sign up to set email alerts
|

‘Mainland-island’ population structure of a terrestrial salamander in a forest-bocage landscape with little evidence for in situ ecological speciation

Abstract: Adaptation to different ecological environments can, through divergent selection, generate phenotypic and genetic differences between populations, and eventually give rise to new species. The fire salamander (Salamandra salamandra) has been proposed to represent an early stage of ecological speciation, driven by differential habitat adaptation through the deposition and development of larvae in streams versus ponds in the Kottenforst near Bonn (Germany). We set out to test this hypothesis of ecological speciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Landcover-based models, on the other hand, always behaved similarly between regions, improving, although slightly, genetic differentiation predictions from IBD models in the ICS and MTR (Table S5). If we consider this together with the fact that forest cover had the highest weight in landcover ENMs (Table S6), our results add to the cumulative evidence that forested areas play a key role in genetic connectivity in salamander populations (Cushman 2006;Antunes et al 2018;Emel et al 2019;Lourenço et al 2019;Arntzen and van Belkom 2020).…”
Section: The Relative Role Of Physical and Ecological Isolation In Genetic Differentiationsupporting
confidence: 57%
See 1 more Smart Citation
“…Landcover-based models, on the other hand, always behaved similarly between regions, improving, although slightly, genetic differentiation predictions from IBD models in the ICS and MTR (Table S5). If we consider this together with the fact that forest cover had the highest weight in landcover ENMs (Table S6), our results add to the cumulative evidence that forested areas play a key role in genetic connectivity in salamander populations (Cushman 2006;Antunes et al 2018;Emel et al 2019;Lourenço et al 2019;Arntzen and van Belkom 2020).…”
Section: The Relative Role Of Physical and Ecological Isolation In Genetic Differentiationsupporting
confidence: 57%
“…Nonetheless, subspecies differentiation seems to be maintained in the Eastern ICS by the combined effect of physical and ecological isolation. Examples from S. salamandra ecotypes in which gene flow is restricted by processes of ecological divergence have already been documented in parapatric pond-and stream-breeding fire salamanders across the Kottenforst (Hendrix et al 2017; but see Arntzen and van Belkom 2020).…”
Section: The Role Of Ecological Isolation In "Ecotype" Divergencementioning
confidence: 99%
“…Breeding in stagnant water bodies may be more common in fire salamanders than generally recognized, also in the western subspecies S. s. terrestris (Denoël and Winandy 2014;Arntzen and van Belkom 2020). A comparison of the well-studied situation in the Kottenforst with that in Vienna does not support generalisations about stream-breeding versus pond-breeding populations but suggests that local environmental conditions shape the variation in life history traits.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, genetically divergent subpopulations associated with larval habitat types -ponds versus streams -differ in several life-history traits (Caspers et al 2014;Oswald et al 2020), including movement behaviour (Hendrix et al 2017). The interpretation of this situation as an example of in situ adaptive divergence, possibly a first step in ecological speciation (Steinfartz et al 2007), was recently challenged by Arntzen and van Belkom (2020), who suggested that the genetic data point to a secondary contact of differentiated lineages.…”
Section: Introductionmentioning
confidence: 99%
“…The high speciation rates in this group nevertheless still associates with their diversity in coloration and the role it plays in aposematic mimicry [122,123]. In fire salamanders, the genetic structure between populations inhabiting distinct habitats was hypothesized to reflect nascent ecological speciation [124], although the pattern can be explained by isolation-by-distance [125]. In European amphibians, hybrid zone analyses suggest that speciation proceeds from genomic divergence in allopatry, generating post-zygotic barriers between cryptic species long before the divergence of sexual traits responsible for pre-mating isolation in sympatry [126,127] (see also §4(c)).…”
Section: Sex Chromosomes As Supergenes Of Speciation In Amphibians?mentioning
confidence: 99%